Fecal biomarkers: Non-invasive diagnosis of colorectal cancer - Ding, Qian; Kong, Xiangxu; Zhong, Weilong; Liu, Wentian (Frontiers in Oncology, 2022)
Colorectal cancer (CRC) is the third most common cancer in the world in terms of morbidity and mortality, which brings great health hazards and economic burdens to patients and society. A fecal examination is an effective method for clinical examination and the most commonly used method for the census. It is simple, non-invasive, and suitable for large-scale population screening. With the development of molecular biology, lots of efforts have been made to discover new fecal biomarkers for the early screening of coloretal cancer. In this review, we summarize and discuss the recent advances of fecal biomarkers for CRC screening or diagnosis, including DNA biomarkers, RNA biomarkers, protein biomarkers, gut microbes and volatile organic compounds focusing on their diagnostic evaluation for CRC, which can provide a basis for the further development of new and effective CRC fecal screening and early diagnosis techniques.